VALIDASI MODUL PEMBELAJARAN MATEMATIKA MATERI BANGUN RUANG SISI DATAR BERBASIS ETNOMATEMATIKA MASYARAKAT SUKU SASAK DI SMP - Suratman Wijaya (JURNAL ILMIAH GLOBAL EDUCATION, 2020)
This research which is entitled validity of the mathematics learning module on the ethnomathematics-based material of the Sasak community in junior high school aims to develop module as teaching materials based on Ethnomatematics on the material of build flat side. The research method used is a research development method which is used to produce a developed module and to test the effectiveness. The product developed is a junior high school mathematics module. The validity of module in this research is based on the feasibility of the standard of the material, media and culture module. The quality of the module validity meets the valid criteria in terms of material, media, and culture with scores of 186, 65 and 4 respectively. Thus, the mathematics learning module on the ethnomathematics-based material of the Sasak community in junior high school which is developed in this research is valid.